The Evaluation of Renal Osteodystrophy in Patients on Hemodialysis by Biochemical and Radiological Methods - Sibel Mandıroğlu; Ece Ünlü; Deniz Ayl (Türk Osteoporoz Dergisi)
Aim: We planned this study in order to evaluate the radiological and biochemical parameters that may be useful in the early diagnosis of renal osteodystrophy in the patients with chronic renal failure, prospectively. Meterial and Methods: In this study, 50 cases on hemodialysis due to chronic renal failure were included and 50 cases without renal and bone pathology were included as control group. Serum levels of calcium, phosphate, alkalen phosphatase, βm, osteocalcin (BGP) and intact parathormon (iPTH) were measured. Right hand graphies of both case and control groups were taken by magnifying techniques. Bone mineral densities (BMD) of lumbar vertebra and femur neck were calculated by DEXA method. Results: The average disease duration and the average of duration of hemodialysis of cases were 8.38±5.61years and 6.9±4.01years, respectively. There were signi cant differences between case and control groups in all biochemical parameters, except calcium levels (p<0.05). There were a negative correlation between iPTH and BMD (r=-0.4, p<0.05), and pozitif correlations between iPTH and BGP (r=0.6, p<0.05), and between PTH and β-m (r=0.5, p<0.05). A low level negative but statistically signi cant correlation between dialysis duration and femur neck bone mineral density was determined (r=0.2, p<0.05). There were positive correlations between dialysis duration and PTH levels (r:0.3, p<0.05), and between dialysis duration and β2 m (r=0.4, p<0.05). In the hand graphies, osteopenia, subperiostal resorption, radial artery calci cation and endoosteal resorption were seen. Ostepenia was determined in 80% of our cases, however, subperiostal resorption was found in 58% of patients. The cases that had iPTH levels over than 200 pg/ml and cases that have osteopenia have sensitivity of 93% and spesi ty of 92% for RO diagnosis. Sensitivity and spesi ty for high iPTH-BGP levels were 90.3% and 87%, respectively. Sensitivity and spesi ty in the evaluation of high iPTH-subperiostal resorption were 83.9% and 84.2%, respectively. Conclusion: Measure of iPTH, BMD, BGP and evaluation of hand graphies may be used in early diagnosis and follow-up of RO. (Turkish Journal of Osteoporosis 2013;19: 7-11)